2009
DOI: 10.1007/s10354-009-0699-z
|View full text |Cite
|
Sign up to set email alerts
|

Lymphocyte imbalance in vitiligo patients indicated by elevated CD4+/CD8+ T-cell ratio

Abstract: Vitiligo is a disorder of pigmentation associated with an autoimmune-mediated loss of melanocytes from the epidermis. Humoral immunity and the involvement of cellular immunity have been investigated in the pathogenesis of vitiligo. We evaluated the role of pro-inflammatory cytokines and lymphocyte fractions in peripheral blood in a cohort of Austrian patients with vitiligo. Morning blood samples from 40 patients with vitiligo were collected. Twenty-one patients had active and 19 had stable vitiligo disease. Al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
48
1
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 22 publications
2
48
1
2
Order By: Relevance
“…Total T-cells were relatively higher in generalized than in acral/acrofacial vitiligo, and CD45RO + T-cells were higher in acral/acrofacial disease. Unlike former studies, Pichler et al [154] found an increased CD4 + /CD8 + ratio in peripheral blood, but noted that the ratio in tissues could be different.…”
Section: Phenotypementioning
confidence: 87%
See 1 more Smart Citation
“…Total T-cells were relatively higher in generalized than in acral/acrofacial vitiligo, and CD45RO + T-cells were higher in acral/acrofacial disease. Unlike former studies, Pichler et al [154] found an increased CD4 + /CD8 + ratio in peripheral blood, but noted that the ratio in tissues could be different.…”
Section: Phenotypementioning
confidence: 87%
“…A recent flow cytometric study of these cells in vitiligo did not show a pathological distribution of B cells, suggesting that T-cells might have a more dominant role. Circulating immune complexes were not elevated either [154]. Cases of generalized vitiligo in recipients of bone marrow transplants from donors with vitiligo have been reported, illustrating the role of bone marrow-derived cells in disease pathogenesis [155].…”
Section: Vitiligo and Autoimmunitymentioning
confidence: 96%
“…Regarding the autoimmune hypothesis, antibodies develop against melanocyte surface antigens (Mahmoud et al, 2008 and their components (Yaghoobi et al, 2011b). In a study, an elevated ratio of CD4 + /CD8 + T cells was seen, which was a sign of imbalanced lymphocyte immune response (Pichler et al, 2009). In another study, small amount of IgG and C3 deposits in the basement-membrane zone and keratinocytes were seen in vitiligo lesions .…”
Section: Etiology and Pathogenesis Of Vitiligomentioning
confidence: 97%
“…Table 3. Disorders associated with vitiligo (Alkhateeb et al, 2003;Birlea et al, 2008;Bolognia et al, 2008;Burn's et al, 2004;Daneshpazhooh et al, 2006;James et al, 2006;Lebwohl et al, 2006;Pichler et al, 2009;Yaghoobi et al, 2011b;Zhang et al, 2009) …”
Section: Association Between Vitiligo and Other Disordersmentioning
confidence: 99%
“…The CD4/CD8 lymphocyte ratio in blood is used in the diagnosis of HIV infection [8][9][10], evaluation of pathogenesis of HCV infection [11] and autoimmune disorders such as rheumatoid arthritis or vitiligo [12,13]. The present study aimed to evaluate changes in the numbers and proportions of the peripheral blood B, NK, T CD3 + , T CD4 + and T CD8 + lymphocyte subsets, and CD4/CD8 ratio following repeated intravenous cocaine administration in rats.…”
Section: Introductionmentioning
confidence: 98%